2009
DOI: 10.1063/1.3169508
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocating flow-based centrifugal microfluidics mixer

Abstract: Proper mixing of reagents is of paramount importance for an efficient chemical reaction. While on a large scale there are many good solutions for quantitative mixing of reagents, as of today, efficient and inexpensive fluid mixing in the nanoliter and microliter volume range is still a challenge. Complete, i.e., quantitative mixing is of special importance in any small-scale analytical application because the scarcity of analytes and the low volume of the reagents demand efficient utilization of all available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…Other applications of pneumatic pumping include its use in rapid mixing of fluids in microsystems (Kellogg and Carvalho 2003;Noroozi et al 2009). In Noorozi et al, the authors showed efficient mixing by oscillating fluids through a mixing chamber by repeated pneumatic pumping and centrifugation (Noroozi et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other applications of pneumatic pumping include its use in rapid mixing of fluids in microsystems (Kellogg and Carvalho 2003;Noroozi et al 2009). In Noorozi et al, the authors showed efficient mixing by oscillating fluids through a mixing chamber by repeated pneumatic pumping and centrifugation (Noroozi et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In Noorozi et al, the authors showed efficient mixing by oscillating fluids through a mixing chamber by repeated pneumatic pumping and centrifugation (Noroozi et al 2009). Their system addresses a key issue in microfluidics as micromixing becomes difficult in the microdomain due to low Reynolds numbers and hence predominately laminar flow.…”
Section: Resultsmentioning
confidence: 99%
“…Centrifugal microfluidics offers the benefit that the force field can be accurately controlled over several orders of magnitude by a spindle motor 1 . Such 'Lab-on-aDisc' (LoaD) platforms have emerged as a highly useful tool in biomedical diagnostics because many of the necessary laboratory unit operations (LUOs) in bioanalysis, such as pumping 2 , plasma extraction 3 , mixing 4 , and metering 5 , can be fully automated and implemented. Liquid-handling steps can then be controlled by running a designated spin-frequency protocol to modulate interactions between on-disc liquids and microstructures 1 .…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the surface treatment and external manipulation of plastics, several new actuation mechanisms have been proposed to optimize the use of real estate on a CD-like chip. These new mechanisms include pneumatic pumping, 6,7 suction-enhanced, 8 and supernatant decanting methods. 9 As pointed out in Ref.…”
Section: Introductionmentioning
confidence: 99%